2020
DOI: 10.1038/s41467-020-15449-9
|View full text |Cite
|
Sign up to set email alerts
|

The translational landscape of ground state pluripotency

Abstract: Translational control plays a central role in regulation of gene expression and can lead to significant divergence between mRNA-and protein-abundance. Here, we used genome-wide approaches combined with time-course analysis to measure the mRNA-abundance, mRNAtranslation rate and protein expression during the transition of naïve-to-primed mouse embryonic stem cells (ESCs). We find that the ground state ESCs cultured with GSK3-, MEKinhibitors and LIF (2iL) display higher ribosome density on a selective set of mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 78 publications
(103 reference statements)
2
13
0
Order By: Relevance
“…We applied poly-A RNA-Seq to both polysome and sub-polysomal (here referred to as ‘monosome’) fractions and analyzed our data with the anota2seq algorithm (Oertlin et al, 2019). Anota2seq identifies changes in polysome vs monosome association of mRNAs leading to three different regulatory outcomes: changes in mRNA abundance, changes in mRNA translation, and mRNA buffering, a process by which changes in mRNA abundance are counteracted at the translation level (or vice versa) in order to preserve protein levels (Atlasi et al, 2020; Blevins et al, 2019). In line with CSDE1 roles in translation regulation and mRNA stability, we found many genes regulated at both levels (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…We applied poly-A RNA-Seq to both polysome and sub-polysomal (here referred to as ‘monosome’) fractions and analyzed our data with the anota2seq algorithm (Oertlin et al, 2019). Anota2seq identifies changes in polysome vs monosome association of mRNAs leading to three different regulatory outcomes: changes in mRNA abundance, changes in mRNA translation, and mRNA buffering, a process by which changes in mRNA abundance are counteracted at the translation level (or vice versa) in order to preserve protein levels (Atlasi et al, 2020; Blevins et al, 2019). In line with CSDE1 roles in translation regulation and mRNA stability, we found many genes regulated at both levels (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…Cell Reports 38, 110211, January 11, 2022 versus monosome association of mRNAs, leading to three different regulatory outcomes: changes in mRNA abundance; changes in mRNA translation; and mRNA buffering, a process by which changes in mRNA abundance are counteracted at the translation level (or vice versa) in order to preserve protein levels (Atlasi et al, 2020;Blevins et al, 2019). Buffering counteracts dramatic changes in gene expression in order to preserve cell state.…”
Section: Regulation Of Translation By Csde1 During Senescencementioning
confidence: 99%
“…Put another way, no specific miRNA "suddenly appears" at the onset, or propagation of AD, and it is a matter of up-regulation or down-regulation of an already existing miRNA species in a specific anatomical region that has been the most consistently observed in the AD brain. Interestingly, very recent moleculargenetic studies have indicated that even when derived from cell and tissue sources that are homogenous, such as pluripotent stem cells, individual cells in these unique populations often exhibit significant differences in miRNA abundance and complexity, gene expression, protein abundance and phenotypic output; here individual families of miRNAs appear to have a deterministic role in reconfiguring the "pluripotency network" and miRNA-mRNA linking patterns in individual cells with important downstream functional consequences (Li et al, 2015;Liu et al, 2015;Atlasi et al, 2020;Chakraborty et al, 2020;Kumar and Reddy, 2020).…”
Section: Microrna (Mirna) and Progressive Inflammatory Neurodegenerationmentioning
confidence: 99%